Analisis Finansial Usaha Peternakan Kambing (Capra Hircus) dan Domba (Ovis Aries) di Masa Pandemi Covid-19 di Kecamatan Wuluhan Kabupaten Jember - Yanu Ramadhan, Angga; Kurniawan, Deddy (Program Studi Agribisnis, 2022)
This researchaims to determine the financial value of goat and sheep business, to compare goat and sheep livestock business finances, and to determine the effect of the COVID-19 pandemic on the finances of goat and sheep farming. This research was conducted on the goat and sheep business in the district Wuluhan, Jember regency in January 2021. This researchuses the method of financial analysis, namely analysis of fixed costs, variable costs, revenue, income, and R/C ratio, and BEP (Breack Even Point). The higher the scale of market demand, the higher the income. Differences receipts and income from goats and sheep, the differences are more.The financial results of goat and sheep business in 2019,2020 have increased, where in 2019 the income of goats is 27,437,000, and sheep income is 30,413,000. Big goat income 49,493,000, sheep income 38,237,000. The R/C of the goat breed ratio is 1.3 and the sheep ratio is 1.4. This states that this livestock business is very feasible to do.